PENGGUNAAN LKS SEBAGAI SUMBER BELAJAR MATEMATIKA DI TKIT QURRATA A’YUN KANDANGAN KALIMANTAN SELATAN - Nor Asyriah (Institut Agama Islam Darul Ulum Kandangan, 2020)
This study aims to see the conformity of LKS made by teachers with the scope of thinking power to be achieved in mathematics learning in kindergarten and see if the stages of mastery of numeracy in the mathematical path have been fulfilled. The type of research used is descriptive with a qualitative approach. The subjects of this study are class teachers. Data in the form of LKS as a source of learning mathematics at TKIT Qurrata A'yun Kandangan. Data collection were carried out by interviews and documentation. The results showed that 1) LKS made by the teacher are in accordance with the scope of the cognitive to be achieved in mathematics learning in kindergarten, but there is still a need for innovations such as designs and pictures that must be presented in a more attractive and colorful; 2) the stages of mastery of counting in the math aspect was fulfilled, such as understanding the concept, the transition period, and symbols.